The Effect of KOH Concentration Variations on the Physical Characteristics of Liquid Dishwashing Soap Made From Tangenore Peel Charcoal (Citrus Reticulata) - Salima Aurelia; Siti Fatimah (Jurnal Multidisiplin Sahombu, 2026)
Orange peel waste, which is usually wasted, has great potential as a value-added raw material. Orange peel contains natural compounds with antimicrobial properties and is able to remove oil and dirt, making it an ideal ingredient for soap making. This study examined the effect of varying KOH concentrations on the physical characteristics of liquid dishwashing soap made from tangerine peel charcoal (Citrus reticulata). The charcoal was produced through a carbonization process using varying temperatures (150°C, 175°C, and 200°C). The liquid soap was then formulated with varying KOH concentrations (12%, 14%, and 16%) and tested for physical characteristics including viscosity, organoleptic properties, homogeneity, foam stability, and pH. The results are expected to determine the optimal formulation of high-quality liquid soap and provide innovative solutions for managing organic waste into sustainable, value-added products.